(3cJGH aj CUhd Gdabgs - (3GdbhLGfjs
(3ChdgG (B:s
.. (3aGdeQLM gh GdHQGAI cGdTc aj CUd GdJcdja hdYdg cPdc bGd aGage hYdi GdKGfj HEjQGOGJ CMOgG Cf JMUjd GdaQV EeG eecf hEeG ZjQ eecf aYdi GdChd jCJj Gdecda HGdCcKQ dJMUjdg hYdi GdKGfj jchf (B...s
(3BNQgG (B:s
.. (3hYfO GdYQa CVjG deG jchf efJSHG HGdejJ GdYGde ef GdCbhGd hZjQfG GMJQGe HNdGa eG jchf efJSH Edi GdMj GdZjQ GdehUha HGdChUGa GdeYJHQI (B.(3bO JeJs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3CUhd Gdabgs